Legal Remedies for Mental Health Issues of Persons Called to Priesthood and Consecrated Life - Gałkowski, Tomasz (Prawo Kanoniczne, 2025)
Admission to a seminary or institute of consecrated life requires candidates to be in an appropriate state of both physical and mental health. Health issues may arise during initial or ongoing formation. This study presents the legal remedies available to superiors, as well as the procedures that allow for reconciling the fulfillment of a vocation with the requirements and responsibilities within the Church community.